Lowering the barriers to sexual health services: Impacts of free counselling and testing for sexually transmitted infections in Switzerland – an observational study - Leonie Arns-Glaser; Andrea Farnham; Katja Hochstrasser; Jan S. Fehr; Benjamin Hampel (PLoS ONE, 2026)
Background In Switzerland, tests for HIV and sexually transmitted infections (STIs) are usually not covered by health insurance in asymptomatic people. To improve access, Zurich launched free voluntary counselling and testing (VCT) in June 2023 for residents <26 years or with low income. This study describes the implementation of free VCT for HIV and STIs in a high-income setting where access to testing was previously expensive, along with key barriers and enablers to accessing testing and counselling in the target population. Methods We conducted a study using routine health data, and a client feedback questionnaire (FBQ) collected during the first 12 months of the programme. Logistic regression models were used to assess factors associated with first-time HIV or STI testing, with results reported as odds ratios (ORs) and 95% confidence intervals (CIs). Results In the first year, 3,475 people came for free testing. 83% (n = 2,866) agreed to share their data. 21% (n = 719) completed the FBQ. Median (IQR) age of participants was 24 (23, 26) years. 46% were assigned female at birth. Four HIV diagnoses were confirmed, all of them in MSM. The infection with the highest positivity rate was chlamydia (4.5%), followed by gonorrhoea (2.5%). Men having sex with men (MSM) showed the highest positivity rate in all STIs. 39% of visits were by individuals who had not received prior HIV testing. MSM were significantly less likely to be first-time testers for HIV (OR: 0.28, 95% CI: 0.15–0.48) and also less likely to be first-time testers for STIs (OR: 0.74, 95% CI: 0.44–1.21) compared to women who have sex with men (WSM); however, the latter association was non-significant. Conclusions The free VCT project experienced high demand during the first year. Even in a high-income setting, counselling improved participants’ sexual health knowledge and facilitated many first HIV/STI tests.